Action Research for Transformative Climate Change Education: Rethinking Sayings, Doings, and Relatings at One Canadian School - Leite, Stephanie (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
This paper documents the action research process at a secondary school in Québec, Canada. Our goal was to rethink sayings, doings, and relatings towards transformative climate change education (TCCE). For schools to play a role in climate action, climate change education must move beyond information-based learning approaches, yet how to practice more transformative approaches remains a question. To pursue this question, this study focuses on action research as a methodology for intervening in different layers of school systems to promote TCCE. This paper applies the theory of practice architectures as an analytical lens to identify the enablers and constraints for holistic change. The study surfaced a complex web of interconnections between individual teacher practices and institutional structures, illuminated challenges of teacher-led school transformation, and demonstrated the promise of participatory action research as a methodology for moving schools towards TCCE.